The temple complex at Horvat Omrit - Overman, J. Andrew, 1955-; Schowalter, Daniel N., 1957-; Nelson, Michael C., 1965- (The Brill Reference Library of Judaism, 2015)
Volume One of The Temple Complex at Horvat Omrit presents a detailed examination of the surviving architecture of the three Roman period temple phases at the newly excavated sanctuary at the archaeological site of Omrit in northern Israel. All three temples were built according to the Corinthian order and the author describes and illustrates the state of the remains, proposes reconstructions of each phase, and places each temple in the broader historical context.